Diagnostic Value of Systemic Inflammatory Response Index for Catheter-Related Bloodstream Infection in Patients Undergoing Haemodialysis - Jiajia Yang; Hongmei Wang; Qing Hua; Jian Wu; Ying Wang (Journal of Immunology Research)
Objective. This study was aimed at investigating the diagnostic value of the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), C-reactive protein-to-albumin ratio (CAR), and systemic inflammatory response index (SIRI) for catheter-related bloodstream infection (CRBSI) in patients undergoing haemodialysis. Methods. A total of 296 patients undergoing haemodialysis with vascular access were selected and divided into the infected (58 patients) and uninfected (238 patients) groups. Their aetiological and general characteristics were retrospectively collected. The NLR, PLR, CAR, and SIRI were calculated. Results. The NLR, PLR, CAR, and SIRI values in the infected group were significantly higher than those in the uninfected group (P<0.05). After the anti-infective treatment, the NLR, PLR, CAR, and SIRI values in patients with CRBSI were significantly decreased (P<0.05). The NLR, CAR, and SIRI showed diagnostic efficacy in patients with CRBSI with cut-off values of 4.485 (area under the curve AUC=0.827, 95%confidence interval CI=0.768–0.887), 0.975 (AUC=0.836, 95%CI=0.779–0.892), and 3.390 (AUC=0.947, 95%CI=0.919–0.976). The CAR and SIRI values in patients with gram-negative bacterial infection were significantly higher than those with gram-positive bacterial infection (P<0.05). The AUCs of CAR and SIRI were 0.693 (0.537–0.848) and 0.821 (0.700–0.942) in differentiating gram-negative and gram-positive bacterial infections, respectively. Conclusion. Our results showed SIRI as a novel and efficient indicator for the early diagnosis of CRBSI in patients undergoing haemodialysis.